2015
DOI: 10.3174/ajnr.a4601
|View full text |Cite
|
Sign up to set email alerts
|

Normal Venous Phase Documented during Angiography in Patients with Spinal Vascular Malformations: Incidence and Clinical Implications

Abstract: BACKGROUND AND PURPOSE:A key angiographic sign observed in patients with spinal vascular malformations is the absence of a normal venous phase. While this finding alone is often believed to rule out a lesion impacting the perimedullary venous drainage, the observation of a venous phase in several patients with vascular malformations led us to reconsider the validity of that sign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The angiographic features of spinal cord parenchymal venous drainage in AESA contrasts with those seen in cases of an AV shunt with medullary venous hypertension (ie, spinal dural AVF) in which there is an absent or delayed angiographic appearance of the veins serving the affected spinal cord segments. 14 Marked arterial ectasia, out of proportion to venous ectasia, is another diagnostic hallmark of AESA. In our series, catheter-directed DSA shows ectasia and tortuosity of the anterior spinal artery and corresponding central sulcal perforators.…”
Section: Discussionmentioning
confidence: 99%
“…The angiographic features of spinal cord parenchymal venous drainage in AESA contrasts with those seen in cases of an AV shunt with medullary venous hypertension (ie, spinal dural AVF) in which there is an absent or delayed angiographic appearance of the veins serving the affected spinal cord segments. 14 Marked arterial ectasia, out of proportion to venous ectasia, is another diagnostic hallmark of AESA. In our series, catheter-directed DSA shows ectasia and tortuosity of the anterior spinal artery and corresponding central sulcal perforators.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Eckart Sorte et al, they concluded that the mere observation of a normal venous phase cannot be used to exclude the presence of a vascular malformation or justify interrupting a diagnostic spinal angiogram. 8 However, demonstration of venous phase/perimedullary veins is very useful and improves the understanding of venous system anatomy and hemodynamics.…”
Section: Discussionmentioning
confidence: 99%